Electronic Properties of Fe3-xCoxO4 (x = 0.25 and 0.375) Synthesized from Natural Iron Sand: Evaluation of Band Gap and Urbach Tail - Saputra, Kormil; Inayah, Rahmatun; Aminy, Ika Umratul Asni; Ardianto, Teguh; Kurniawidi, Dian W. (Universitas Jenderal Soedirman, 2025)
Fe3-xCoxO4 nanoparticles (x = 0.25 and 0.375) were successfully synthesized using natural iron sand as the base material through a coprecipitation method with the addition of CoCl2·6H2O as a cobalt source. Optical characterization was carried out using UV–Vis spectroscopy in the wavelength range of 200–800 nm to analyze the electronic properties of the material. The measurement results showed that increasing the cobalt fraction strengthened the absorption in the visible region and shifted the absorption onset to lower energies, indicating a narrowing of the band gap energy. Tauc analysis revealed that the direct gap energy decreased from 2.271 eV (x = 0.25) to 2.221 eV (x = 0.375), while the indirect gap energy decreased from 2.222 eV to 2.204 eV. Furthermore, the Urbach energy calculation shows an increase from 0.073 eV at x = 0.25 to 0.074 eV at x = 0.375, indicating an increase in local disorder that broadens the band tail. This finding is consistent with previous research reports on Co-doped magnetite and CoFe2O4, and confirms that cobalt doping is effective in enhancing the visible light absorption capacity. Thus, Fe3-xCoxO4 based on natural iron sand, especially at x = 0.375, has potential applications as an active material in visible light-based photocatalysis and solar energy optoelectronic devices.